2011
DOI: 10.1016/j.fertnstert.2011.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Divergent effects of a combined hormonal oral contraceptive on insulin sensitivity in lean versus obese women

Abstract: Objective To evaluate the effects of a commonly used combined hormonal oral contraceptive (OC) on carbohydrate metabolism in obese as compared with obese women. Design 6-month prospective study. Setting Clinical Research Center at an academic medical center. Patients Premenopausal non-diabetic women with BMI < 25 kg/m2 (n=15) or > 30 kg/m2 (n=14). Intervention Ethinyl estradiol 35mcg and norgestimate 0.18/0.215/0.25 mg for 6 cycles. Main Outcome Measures Insulin sensitivity (Si) by frequent sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…In a recently published study, no statistically significant difference was observed in the fasting glucose levels between obese and normal-weight women during three months of intervention (30). Similarly, in a study by Cheang et al, there were no significant differences in FPG between lean and obese women after six months (31). These findings may indicate that the changes in carbohydrate metabolism in overweight and obese women are similar to those of normal-weight women who take COCs.…”
Section: Discussionmentioning
confidence: 79%
“…In a recently published study, no statistically significant difference was observed in the fasting glucose levels between obese and normal-weight women during three months of intervention (30). Similarly, in a study by Cheang et al, there were no significant differences in FPG between lean and obese women after six months (31). These findings may indicate that the changes in carbohydrate metabolism in overweight and obese women are similar to those of normal-weight women who take COCs.…”
Section: Discussionmentioning
confidence: 79%
“…The other study evaluated the OC in regular cycling women without PCOS exclusively (NCT00205504). 9 Both the previous studies and the present study were approved by the Virginia Commonwealth University Institutional Review Board. All study participants provided informed consent.…”
Section: Participantsmentioning
confidence: 99%
“…All study participants provided informed consent. For this report, we included all PCOS women randomized to OC, but not metformin (from NCT00682890) 24 and matched their BMI to normal women (from NCT00205504) 9 using the nearest neighbor method. All subjects included in this report were overweight or obese.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations